Molecular detection of blaOXA-23gene and blaOXA-51 gene in carbapenem resistant strains of Acinetobacterbaumannii in patients with ventilator associated pneumonia at tertiary care hospital - Saima Ishtiaq; Sidrah Saleem; Abdul Waheed; Arslan Ahmed Alvi (Journal of the Pakistan Medical Association, 2021)
Objective: To evaluate carbapenem resistance and to detect blaOXA-23 and blaOXA-51 genes in carbapenem-resistant acinetobacter baumanii isolates recovered from patients having pneumonia secondry to ventilation. Methods: The cross-sectional study was conducted from July 2017 to June 2018 at the Department of Microbiology, University of Health Sciences, Lahore, Pakistan, and comprised endotracheal aspirates / tracheobroncheal lavage samples from patients irrespective of age and gender who developed pneumonia after being on the ventilator for 48 hrs at the Combined Military Hospital, and Jinnah Hospital, Lahore. The samples were inoculated on MacConkey and blood agar and aerobically incubated at a temperature of 370C for 18-24 hours. The isolated organisms were further assessed by standard morphological, cultural and biochemical profile. Antibiotic susceptibility was done by Kirby-Bauer disc diffusion method. Carbapenem-resistant acinetobacter baumannii were checked for carbapenemase production using Modified Hodge Test. Conventional polymerase chain reaction and agarose gel electrophoreses were performed to detect blaOXA-23 and blaOXA-51 genes. Data was analysed using SPSS 17. Results: Out of 157 samples, 92(58.6%) yielded growth of bacteria, and, among them, 39(42.4%) were identified as acinetobacter baumannii. All (100%) acinetobacter baumannii cases showed resistance to carbapenem, were producing carbapenemase enzyme, and were positive for blaOXA-51 gene. The blaOXA-23 gene was amplified in 38(97.4%) isolates. Conclusion: BlaOXA-23 gene appeared to be the major cause of carbapenem resistance. Continuous...